Memórias de infância: pesquisa poética em artes visuais - Arend, Aline (2016)
The present Dissertation approaches a study about the artistic construction from the rescue of childhood memories. Its corpus concerns an autobiographic research, which have sought for elements from the long-term memory along with photographs and personal belongs stocked by the artist, enabling a reflection about mechanisms, restlessness and personal reflections in the face of the contemporary art practice. It is presented the poetic construction from artist s books and object books. Mentions about the metal engraving technical procedures are present in this study, since they are an active part of the process of building autobiographical elements from childhood memories. It was created ten works from this research, which were divided in: a unique work (artist s book) called Memory s album and other four series (artists book and object-books). They are: Ways, White Clouds in a Reddish Sky, The Hallway s Corner e The Toy Room.